An Insight into the Properties of a Two-Stage Design in Bioequivalence Studies - Karalis, Vangelis; Macheras, Panos (PHARMACEUTICAL RESEARCH, 2013)
Unveil the properties of a two-stage design (TSD) for bioequivalence (BE) studies. A TSD with an upper sample size limit (UL) is described and analyzed under different conditions using Monte Carlo simulations. TSD was split into three branches: A, B1, and B2. The first stage included branches A and B1, while stage two referred to branch B2. Sample size re-estimation at B2 relies on the observed GMR and variability of stage 1. The properties studied were % BE acceptance, % uses and % efficiency of each branch, as well as the reason of BE failure. No inflation of type I error was observed. Each TSD branch exhibits different performance. Stage two exhibits the greatest % BE acceptances when highly variable drugs are assessed with a low starting number of subjects (N-1) or when formulations differ significantly. Branch A is more frequently used when variability is low, drug products are similar, and a large N-1 is included. BE assessment at branch A is very efficient. The overall acceptance profile of TSD resembles the typical pattern observed in single-stage studies, but it is actually different. Inclusion of a UL is necessary to avoid inflation of type I error.
Keywords: adaptive design; bioequivalence; Monte Carlo simulations; Sample Size; two-stage design